Criminal Legal Protection Formulation Policy Towards Victims Of Criminal Acts In The Medical Field - Widiyanto, Endra (Universitas STRADA Indonesia, 2024)
In fact, the officer cannot be blamed if he asks the patient whether he has money or not, but not because he is worried that the patient will not pay for the treatment/care, but because there is a fairly expensive prescription that must be filled at the pharmacy. In addition, the hospital is always blamed if there are bad consequences for the patient that occur during or after receiving treatment/care/medical actions in the form of a worsening condition of the disease, injury or even death. However, in fact, these complaints cannot be ignored so as not to cause prolonged and tiring legal conflicts. The objectives of this study are: (1) To describe the policy of formulating criminal law protection for victims of criminal acts in the medical field today. (2) To analyze the policy of formulating criminal law protection for victims of criminal acts in the medical field in the future. The type of approach used in this study is normative juridical. The data sources used in this study are primary legal materials, secondary legal materials and tertiary legal evidence. The data collection technique uses literature studies, including documentaries. Data analysis is normative-qualitative by interpreting and constructing statements contained in documents and legislation. The conclusion of this study is: (1) The policy of formulating legal protection for victims of medical crimes in positive criminal law in Indonesia, namely based on the Criminal Code, Law No. 36 of 2014 concerning Health, Law. No. 29 of 2004 concerning Medical Practice, apparently still has weaknesses. The weaknesses of the formulation policy are: (a) Formulation of medical crimes. (b) The formulation of responsibility for medical crimes can have individual or corporate legal subjects. (c) Formulation of criminal and criminal penalties in positive criminal law. (2) The policy of formulating legal protection for victims of medical crimes, criminal law in Indonesia is expected to provide a formulation of protection for victims in the form of guarantees/legal compensation for suffering/losses and also a formulation of legal protection not to become victims of similar crimes. The policy formulation of protection for victims of medical crimes in criminal law in Indonesia is as follows: (a) Through the policy of reformulation and reorientation of criminal law in the field of health and medical practice. (b) Based on the basic idea or principle of the idea of ​​balance.